Pengunduran Diri Kurator dalam Praktek Pengadilan Niaga - Togar Sahat Manaek Sijabat; Enaz Olyna Sijabat; Antonius Alreza Pahlevi Marulitua; Kris Lihardo Aksana Sijabat (CV Rewang Rencang, 2024)
In the practice of bankruptcy where the management and settlement are carried out by a Curator, it is often heard that the Curator handling the bankruptcy case resigns or a request for replacement is submitted by another party. Replacement of the curator in the bankruptcy process can be done by submitting a request to the Commercial Court. The court will summon and listen to the curator concerned, then decide to replace or appoint a new curator. Replacement of the curator can be done based on several considerations, including: Application of the curator himself, Application of another curator, Proposal of the Supervisory Judge, Request of the bankrupt debtor. The curator is appointed by the Court together with the appointment of the Supervisory Judge. The curator's task is to manage and settle the bankrupt's assets since the bankruptcy decision was pronounced.